IDENTIFIKASI JENIS KANTONG SEMAR (NEPENTHES SPP) DALAM KAWASAN TAMAN WISATA ALAM GUNUNG ASUANSANG KECAMATAN PALOH KABUPATEN SAMBAS - Mardianto, .; Fahrizal, .; Dirhamsyah, M. (JURNAL HUTAN LESTARI, 2016)
Nepenthes is one of plant’s the uniq and spesific. The uniqueness and of that found on the bag's existence is a modification from the ends of the leaves of this plant, so called by the Pitcher Plant. In Indonesia plant better known as Nepenthes belongs to family Nepenthaceae, that comprises 82 types around the world, the center of the spread of the world's largest Nepenthes of which are found in Borneo and Sumatra.  The purpose of this research is to know the species of Nepenthes are contained within the Park area Asuansang Mountain nature tourism Sub Paloh Regency Sambas.  Method’s is carried out using the exploration area in the thorough, in conducting the observation made five cruise lines with the length, direction and distance varies on each track. The fifth track is track 1, track 2, track 3, track 4 and track 5. After identifying found type of Nepenthes sebayak five types for the entire path i.e. n. ampullaria jack, n. gracilis korth. N. mirabilis (Lour) Druce. N. rafflesiana jack. N. echinostoma, from 149 individuals. Types that are often encountered in 5 lines of observation is the type of n. Gracilis korth and n. Mirabilis (Lour) Druce and there are also 4 types of aliens into the status of IUCN (International Union for the Conservation of Nature and Natural Resources). that is the type of n. ampullaria jack, n. gracilis korth. N. mirabilis (Lour) Druce. N. rafflesiana jack. Belonging to the category of near threatened LC (Last Concern). Keywords: Nepenthes, Natural Park Of Mount Asuansang, Identification.